Analysis of Malaysia's Policy Towards Indonesian Illegal Immigrants 2020 - 2023 - Febianto; Aslam, Mohd. Mizan Bin Mohammad (Indonesian Scientific Publication, 2025)
This study analyzes Malaysia's immigration policy toward illegal Indonesian migrants during the 2020–2023 period. While Malaysia implemented programs such as the Recalibration Programme to manage undocumented migration, these efforts are considered ineffective due to inconsistent implementation, weak inter-agency coordination, and the absence of comprehensive protection mechanisms for migrant workers. These policy shortcomings have contributed to serious negative consequences, including widespread human rights violations and labor exploitation. The formulation of Malaysia’s immigration policies is shaped by multiple factors, including economic pressures, domestic political considerations, and bilateral relations with Indonesia. The study identifies a shift in Malaysia’s policy orientation—from repressive measures such as mass raids and deportations toward more selective legalization and cooperation-based approaches. However, structural challenges remain, particularly regarding the protection of migrants’ rights and the regulation of recruitment practices. The findings highlight the need for a more integrated and humane bilateral framework to ensure safe, legal, and dignified migration. Strengthening collaboration between both countries and relevant international organizations is essential for achieving long-term regional migration governance.